Novel Influenza H1N1 in Pregnancy: Report of a Diagnosed Case in Bangladesh - Rashid, Maliha; Ara, Rawshan; Akhter, Nasrin (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
Category C pandemic flu 2009 H1N1 influenza), the disease that has reached pandemic proportions, holds everyone at risk today H1N1 influenza and pregnancy together, poses a greater risk for pregnant women and this deserves special attention. A swine flu pregnancy can be life threatening for both the mother and the baby. During the current pandemic of H1N1 influenza, few cases of H1N1 have been reported in pregnancy cases. We report one interesting case of H1N1 influenza, which was the only confirmed case of H1N1 Flu who survived with pregnancy in Bangladesh. Widespread vaccination, when available, prompt diagnosis, and adequate treatment with antiviral medications when infection occurs can save the life of the mother and the baby. Keywords: Novel influenza H1N1; pregnancy Bangladesh J Obstet Gynaecol, 2009; Vol. 24(2) : 75-78 DOI: http://dx.doi.org/10.3329/bjog.v24i2.8533